In vitro probiotic evaluation of phytase producing Lactobacillus species isolated from Uttapam batter and their application in soy milk fermentation - Saraniya, Appukuttan (J Food Sci Technol, 2014)
Probiotic lactic acid bacteria are health promoters and have been traditionally consumed without the knowledge that they have beneficial properties. These bacteria mainly involve in secreting antimicrobials, enhance immune-modulatory effects, and preserve the intestinal epithelial barrier by competitively inhibiting the pathogenic organisms. The aim of this study was to investigate the in vitro probiotic properties of Lactobacillus pentosus, Lactobacillus plantarum, Lactobacillus plantarum ssp. argentoratensis, and Lactobacillus plantarum ssp. plantarum isolated from fermented Uttapam batter. The isolates produced bacteriocins that were effective against several pathogens. All the isolates exhibited tolerance to bile, gastric, and intestinal conditions. Beneficial properties like cholesterol assimilation and production of enzymes such as β-galactosidase, phytase and bile hydrolase varied among the isolates. Four isolates from each sub-species effectively adhered to Caco-2 cells and prevented pathogen adhesion. Using these strains, the soy milk was fermented, which exhibited higher antioxidant activity, 2,2-diphenylpicrylhydrazyl (DPPH) scavenging activity and decreased phytate content when compared to unfermented soy milk. Thus, these probiotic isolates can be successfully used for formulation of functional foods that thereby help to improvise human health.